2019
DOI: 10.1111/liv.14096
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the association of serum ferritin and hepatic iron with disease severity in non‐alcoholic fatty liver disease

Abstract: Background & Aims: Hyperferritinemia, with or without increased hepatic iron, represents a common finding in non-alcoholic fatty liver disease (NAFLD). However, it is unclear whether it reflects hepatic inflammation or true iron-overload and, in case the latter is confirmed, whether this influences disease progression. We therefore explored the association between serum ferritin, degree and pattern of hepatic iron deposition and liver disease severity in patients with NAFLD. Methods:We selected 468 patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
54
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 35 publications
12
54
1
Order By: Relevance
“…Italian study found that the mixed pattern was linked to NASH. 17 Thus, our findings are in support of the relevance of the mesenchymal pattern of iron deposition to be detected in a NAFLD patient.…”
Section: Baseline Disease Severity and Serum Ferritin Differences Bsupporting
confidence: 84%
See 2 more Smart Citations
“…Italian study found that the mixed pattern was linked to NASH. 17 Thus, our findings are in support of the relevance of the mesenchymal pattern of iron deposition to be detected in a NAFLD patient.…”
Section: Baseline Disease Severity and Serum Ferritin Differences Bsupporting
confidence: 84%
“…6 However, the contribution of excess iron in the aimed to assess disease severity and iron with inconclusive and conflicting results. 8,14,15,17,18 Interventional studies, ie iron depletion via phlebotomies, are few and observational, while one well-designed…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, further studies are warranted to understand the real prognostic value of iron deposits at liver biopsy. Interestingly, hyperferritinemia, which probably identifies NAFLD patients with major hepatic iron deposition, has also been demonstrated to be an independent predictor, not only of liver steatosis, but also of fibrosis [199,200,201]. However, it should be mentioned that clinical trials examining the potential therapeutic role of phlebotomy in NAFLD have shown contrasting results regarding any benefits in terms of reduction of liver damage [202,203].…”
Section: Pathophysiological Featuresmentioning
confidence: 99%
“…However, in inflammatory conditions ferritin concentrations are increased and it is synthesized as an acute phase protein, acting as a pro-inflammatory molecule capable of inducing liver damage. [33,35,36,37]. The potential anti-inflammatory effect and antioxidant capacity of omega-3 PUFAs [38], might ameliorate ferritin pro-oxidant and pro-inflammatory activity, although the exact molecular pathways are yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%